A assistência educacional nas prisões: a gestão por organizações sociais e parcerias público-privadas na esteira da reforma do Estado - Bittencourt, Liliana (2019)
The flowing change of Brazilian State’s form brought with it the pressing need to face the concrete outsourcing of traditionally public functions including the administration of prisons. Formal education during imprisonment is one or those administrative functions and one very delicate, complex and poorly understood. The new juridical tools, established by recent laws that aim at privatizing in the new mood, fell under scrutiny in so far as they may or may not be compatible with the task of catering to inmates taken as pupils. Pacts and agreements with non-profits, or contracts to outsource prison maintenance to the private sector may not guarantee the perfect or at least the efficient focus on pedagogy __ or andragogy, for that matter. The issue is multidisciplinary in its nature, and begged considerations in educational philosophy, anthropology, politics, sociology, before a proper study in matters of law could begin. Criminal, procedural, constitutional and administrative laws were called into question in an intermingled approach. The intertwined elements of theory and data gathered through probing questionnaires show that it is not possible, at the moment, to draft a consistent public policy plan on prison educational practices. The lack of relevant sources turns into mere conjectures the relations of cause and effect between education delivered in state-owned penal institutions, or in private administrated prisons, and recidivism rate, employability and, last but not least, personal development. News from Nordic countries are taken at face value from published researches to serve as a touchstone in defining the singularity or generality of the problems found in some Brazilian states. Those countries were chosen in view of their privileged ranking in education assessment.